Real-time IoT-based water quality monitoring system for aquariums / Muhamad Nuaiman Syah Mohd Faizun Syafiq - Mohd Faizun Syafiq, Muhamad Nuaiman Syah (2024)
Monitoring systems have become essential in various domains, ranging from environmental monitoring to quality control. With that being said, the growing popularity of aquariums amplifies the challenges in ensuring consistent water quality. Current manual monitoring falls short, necessitating an innovative approach. This project presents the development of an IoT-based water quality monitoring system for aquariums using Arduino UNO. The work involves hardware installation and construction of prototype of the system. The system is intended to measure temperature and pH level of water. This system consists of temperature sensor, pH sensor, LCD, LED, buzzer, ESP01 and Arduino UNO. The results demonstrate the capability of the water quality monitoring system to effectively measure and monitor water quality parameters. Furthermore, it also exhibits its capability to integrate with IoT cloud/server which is Blynk so that the result can be displayed on the Blynk desktop and mobile dashboard